The Effect of Compound Honey Syrup on Clinical Manifestation of the Adult Asthma Patients: A Randomized, Double-Blinded, Placebo-Controlled Clinical Trial - Shahpar Kaveh; Narges Kaveh; Khosrow Agin; Saeed Sadr; Rasool Choopani; Arian Karimi Rouzbahani (Tehran University of Medical Sciences, 2022)
Asthma is a chronic inflammatory disease of the respiratory tract which includes inflammation and obstruction of the airways. Modern medical treatment has side effects in addition to therapeutic effects. According to the high incidence of asthma, the use of complementary therapies has risen, such as compound honey syrup in Traditional Persian medicine and Integrative medicine as a treatment for asthma. Therefore, the aim of this study was to evaluate the effect of compound honey syrup in improving the clinical symptoms of adult asthma referred to Loghman hospital. This randomized, double-blinded, controlled trial was performed on 80 patients with asthma symptoms. Patients were divided into two groups of 40 and the study was conducted for 12 weeks. The intervention group received classic asthma treatment and compound honey syrup. The control group also received classic asthma treatments plus placebo. The questionnaire was done by individuals at the beginning and end of the study. At the end of study some factors like night symptoms, morning symptoms, activity limitation, shortness of breath, wheezing, and use of Short Acting Beta Agonist (SABA) were significantly decreased in both groups, but it had a greater extent in the intervention group than in the control group. Difference in total scores and some items of Asthma Control Test (ACT) were significant between groups (P < 0.05). No serious adverse effects were observed in any of the groups. The results of this study demonstrate that compound honey syrup can be a safe and effective drug for the treatment of asthma in adults.